Academic career in the Malaysian higher education: Becoming a professor - Sidek, Safiah; Dora, Mohd Taib; Kudus, Norliah; Abu Hassan, Mahadi (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2012)
The promotion to a full professor is the ultimate achievement in the career development of an academic. However, little has been written about the promotion process to a full professor. It has become a common understanding that the criteria for promotion in academic career centres primarily on teaching, research and service. However, due to the changing landscape of higher education shaped by the ease of mobility, internationalisation and emphasis on knowledge society, the promotion criteria has become more diversed and complex. This paper aims to explore the academic career, particularly the profile of a professor within the context of Malaysian higher education. Further, recognising that the higher education policy has an impact on the academic career, the discussion takes into consideration the strategic plan of the national higher education transformation and the guidelines for the tenure and promotion of two categories of professor: the professor and distinguished professor. This discussion is timely, as it will provide guidance for young academics to strategise their career planning in achieving the highest position in their career.